Quantitative comparison on permanent-magnet vernier machines with improved flux modulation effect for automatic guided vehicles - Cao, Libing (2022)
In this paper, the interior permanent-magnet vernier (PMV) machines and the conventional PMV machine are quantitatively compared regarding the requirements for electric automatic guided vehicles (AGV). The key feature of the interior PMV machines is to place the middle iron pole sandwiched by PMs in the slots between the salient rotor poles. As a result, three types of interior PMV machines with different PM arrangements, namely two V-type PMV (V-PMV) and one U-type PMV (U-PMV) machines, are developed. Due to the improved flux modulation effect, the V-PMV and U-PMV machines can respectively provide over 20% and 30% higher torque density than the conventional PMV counterpart, under a high power factor level of 0.86. The working principle is illustrated based on the field modulation theory. A comparative study among the conventional PMV and interior PMV machines is conducted in terms of electromagnetic performances and dynamic responses, after performing global optimization of design parameters. Finally, a prototype is manufactured and tested for experimental validations.